How Do They Deal With Speaking Anxiety?: EFL Learners’ Strategies - Idrus, Misnariah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Emotion promotes various consequences on language learning (Maquidato, 2021). It includes language anxiety. (Brown 2000) defined language anxiety as the "state of mind connected with uneasiness, frustration, self-doubt, or worry". The study aims to investigate how students deal with the condition. This is a qualitative study employing a case study design. I involved twenty university students majoring in English Education as participants. I selected them purposively based on the anxiety symptoms they showed in the observation. Data were obtained through three stages consisting of observation, as I mentioned earlier, focus group discussion, and interviews. After collecting data through the abovementioned procedures, they were analyzed through some stages: data coding, reduction, and grouping. I then compared the findings with earlier findings or theories to get a valid conclusion. Based on the findings and discussion above, I concluded five strategies implemented by EFL learners in coping with speaking anxiety. They are to think positively, start a conversation with a more common topic, shift the communication to a written form, and understand the speaking topic well. Further research should investigate those strategies quantitatively to measure their effectiveness levels.